Controlled Resistant Hypertension Following A Successful Renal Artery Stenting: A Rare Case Report in A Developing Country - Fatihatul Firdaus Munita; Badai Bhatara Tiksnadi; Januar Wibawa Martha; Margareta Ginanti Ratna (Majalah Kardiologi Indonesia)
Background